Targeting DEC-205(−)DCIR2(+) dendritic cells promotes immunological tolerance in proteolipid protein-induced experimental autoimmune encephalomyelitis - Tabansky, Inna (Mol Med, 2018)
BACKGROUND: Dendritic cells (DC) induce adaptive responses against foreign antigens, and play an essential role in maintaining peripheral tolerance to self-antigens. Therefore they are involved in preventing fatal autoimmunity. Selective delivery of antigens to immature DC via the endocytic DEC-205 receptor on their surface promotes antigen-specific T cell tolerance, both by recessive and dominant mechanisms. We provide evidence that the induction of antigen-specific T cell tolerance is not a unique property of CD11c(+)CD8(+)DEC-205(+) DCs. METHODS: We employed a fusion between αDCIR2 antibodies and the highly encephalitogenic peptide 139–151 of myelin-derived proteolipid protein (PLP(139–151)), to target CD11c( +)CD8(-) DCs with a DEC-205−DCIR2(+) phenotype in vivo, and to substantially improve clinical symptoms in the PLP(139–151)-induced model of experimental autoimmune encephalomyelitis (EAE). RESULTS: Consistent with previous studies targeting other cell surface receptors, EAE protection mediated by αDCIR2-PLP(139–151) fusion antibody (Ab) depended on an immature state of targeted DCIR2(+) DCs. The mechanism of αDCIR2-PLP(139–151) mAb function included the deletion of IL-17- and IFN-γ-producing pathogenic T cells, as well as the enhancement of regulatory T (Treg) cell activity. In contrast to the effect of αDEC-205(+) fusion antibodies, which involves extrathymic induction of a Foxp3(+) Treg cell phenotype in naïve CD4(+)Foxp3(-) T cells, treatment of animals with DCIR2(+) fusion antibodies resulted in antigen-specific activation and proliferative expansion of natural Foxp3(+) Treg cells. CONCLUSIONS: These results suggest that multiple mechanisms can lead to the expansion of the Treg population, depending on the DC subset and receptor targeted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s10020-018-0017-6) contains supplementary material, which is available to authorized users.